2021
DOI: 10.1002/essoar.10506144.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust uncertainty quantification of the volume of tsunami ionospheric holes for the 2011 Tohoku-Oki Earthquake: towards low-cost satellite-based tsunami warning systems

Abstract: We develop a new method to analyze the total electron content (TEC) depression in the ionosphere after a tsunami occurrence. We employ Gaussian process regression to accurately estimate the TEC disturbance every 30 s using satellite observations from the global navigation satellite system (GNSS) network, even over regions without measurements. We face multiple challenges. First, the impact of the acoustic wave generated by a tsunami onto TEC levels is nonlinear and anisotropic. Second, observation points are m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…However, Zettergren et al (2017) reported a deeper ionospheric hole in the equatorial direction, due to the poleward/downward transport of plasma from equatorward to poleward. Kanai et al (2022) improved the coverage of TEC data using Gaussian process regression and found that the TEC depletion extends more equatorward than poleward from the epicenter. On the other hand, Otsuka et al (2006) discuss that the acoustic-gravity wave perturbations are more prominent in observations at the equatorward direction than poleward of epicenter due to that the wave fronts are aligned/perpendicular to the magnetic field line at equatorward/poleward direction.…”
Section: Discussionmentioning
confidence: 99%
“…However, Zettergren et al (2017) reported a deeper ionospheric hole in the equatorial direction, due to the poleward/downward transport of plasma from equatorward to poleward. Kanai et al (2022) improved the coverage of TEC data using Gaussian process regression and found that the TEC depletion extends more equatorward than poleward from the epicenter. On the other hand, Otsuka et al (2006) discuss that the acoustic-gravity wave perturbations are more prominent in observations at the equatorward direction than poleward of epicenter due to that the wave fronts are aligned/perpendicular to the magnetic field line at equatorward/poleward direction.…”
Section: Discussionmentioning
confidence: 99%